2019
DOI: 10.1051/0004-6361/201834567
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of hydrocarbons in the bright photodissociation region of Messier 8

Abstract: Aims. Hydrocarbons are ubiquitous in the interstellar medium, but their formation is still not well understood, depending on the physical environment they are found in. Messier 8 (M8) is host to one of the brightest Hii regions and photodissociation regions (PDRs) in our galaxy. With the observed C 2 H and c-C 3 H 2 data toward M8, we aim at obtaining their densities and abundances and to shed some light on their formation mechanism. Methods. Using the Atacama Pathfinder Experiment (APEX) 12 m, and the Institu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Besides, the c-C 3 H 2 abundances in Mon R2 were found to be higher close to the UV-exposed PDR than the C 2 H abundances (Pilleri et al 2013). The formation sequences mentioned above cannot easily result in the high c-C 3 H 2 abundances, and reproducing observed c-C 3 H 2 values with PDR models has been difficult (e.g., c-C 3 H 2 abundances in M8, Tiwari et al 2019). Another possible way to produce c-C 3 H 2 is grain-surface formation via photons.…”
Section: Formation Of Small Hydrocarbons and Observational C-c 3 H 2 /C 2 H Column Density Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the c-C 3 H 2 abundances in Mon R2 were found to be higher close to the UV-exposed PDR than the C 2 H abundances (Pilleri et al 2013). The formation sequences mentioned above cannot easily result in the high c-C 3 H 2 abundances, and reproducing observed c-C 3 H 2 values with PDR models has been difficult (e.g., c-C 3 H 2 abundances in M8, Tiwari et al 2019). Another possible way to produce c-C 3 H 2 is grain-surface formation via photons.…”
Section: Formation Of Small Hydrocarbons and Observational C-c 3 H 2 /C 2 H Column Density Ratiomentioning
confidence: 99%
“…Although those small hydrocarbons are well-known PDR tracers, their abundances vary from one PDR to the other (e.g., Pety et al 2005;Mookerjea et al 2012;Pilleri et al 2013;Cuadrado et al 2015;Tiwari et al 2019). By investigating their abundances for ATLASGAL clumps, we may gain insight into the origin of the detected small hydrocarbons (i.e., C 2 H and c-C 3 H 2 ).…”
Section: Formation Of Small Hydrocarbons and Observational C-c 3 H 2 /C 2 H Column Density Ratiomentioning
confidence: 99%
“…In the Orion Bar PDR, close to the Orion nebula, high abundance of small hydrocarbons was explained by high-temperature chemical reactions involving excited hydrogen molecules (Agúndez et al 2010;Cuadrado et al 2015). Also, no discrepancies were found between the observed abundances of C 2 H and the results of the astrochemical modelling in the M8 PDR by Tiwari et al (2019). Murga et al (2020) showed that an effective formation of C 2 H from acetylene molecules (C 2 H 2 ) occurs as a result of photo-destruction of PAHs in the Orion Bar PDR, while in the Horsehead this process is practically insignificant in comparison to the formation of C 2 H via gas-phase reactions starting from ionised carbon C + .…”
mentioning
confidence: 84%
“…UV radiation, if sufficiently intense, produces photondominated regions (PDRs). In PDR chemistry, small hydrocarbons such as c-C 3 H 2 can be abundant in less shielded regions (e.g., A v ∼ 1.43 mag; Tiwari et al 2019), while CH 3 OH formation is efficient in more shielded regions (A v > 2 mag; Esplugues et al 2019). In order to investigate the effects of UV irradiation from the nearby Herbig Be star on Oph-emb9, we derive the N (c-C 3 H 2 )/N (CH 3 OH) ratio at each position as summarized in Table 4.…”
Section: Comparison Of the N (C-c3h2)/n (Ch3oh) Ratio Derived From Ca...mentioning
confidence: 99%